Contextualizing Organizational Justice: How Project Teams Experience Fairness at Work in a Pakistani Mega Construction Project (Journal of Asian Development Studies, 2025)
This study investigates how project team members in Pakistani project-based organisations (PBOs) perceive and experience organisational justice in a culturally integrated context. The research addresses a gap in the literature by applying a qualitative, interpretivist methodology, utilising a diary-interview design with 20 project team members. Data was collected through real time diary entries over four weeks and supplemented by semi-structured interviews to provide a holistic understanding of justice dynamics. The findings indicate that perceptions of justice are influenced by five main elements: favouritism, communication style, behaviour, transparency in decision-making, and socio-cultural hierarchy. The study further found that interactional justice, which is based on respectful communication and emotional recognition, is the most culturally and emotionally significant dimension of fairness in Pakistani project environments. The study contributes to the theoretical understanding of organisational justice by providing a culturally grounded perspective that challenges the generalizability of Western models and offers practical implications for project managers seeking to foster fairness in culturally diverse and dynamic work settings.